Enhancing Durability in Recycled Concrete: Investigating Chloride Permeability with Recycled Aggregates and Plastic Waste - Jantarachot, Krissana; Prayongphan, Somchai; Yodsudjai, Wanchai; Thepjunthra, Wiphada; Trakolkul, Chokchai; Thongchart, Siranya (Salehan Institute of Higher Education, 2025)
This study investigates the effects of substituting fine aggregates with recycled plastic in recycled concrete, focusing on chloride penetration, compressive strength, workability, and porosity. Recycled plastic was incorporated at 10% (A10) and 20% (A20) by volume, and properties were evaluated across six mix designs. The control mix without plastic (Mix A) achieved the highest 28-day compressive strength (400 KSC), while A10 and A20 showed reduced strengths of 320 and 255 KSC, respectively. The addition of plastic increased mix porosity, resulting in reduced strength and workability due to diminished cement bonding and lubrication. Chloride ingress was assessed under cyclic wetting–drying exposure using a 3.5% NaCl solution. Results revealed progressive surface chloride accumulation over time. Notably, Mix A showed a 137.96% increase in chloride content at a 0–2 cm depth after 280 days, with Mix A20 exhibiting even higher surface concentrations. Chloride content consistently decreased beyond a 4 cm depth, indicating limited long-term penetration into inner layers. These findings highlight the importance of porosity control in mitigating chloride transport in recycled concrete. A clear relationship between plastic content, increased porosity, and enhanced chloride diffusion was observed. While 10% plastic substitution demonstrated acceptable performance, higher levels significantly compromised durability. The study recommends limiting plastic waste incorporation to 10% by volume and maintaining a concrete cover of at least 8–10 cm over reinforcement to enhance resistance against chloride-induced corrosion. These findings support the controlled reuse of plastic waste in sustainable concrete development, particularly for non-structural or low-exposure applications. Optimizing mix design and incorporating supplementary cementitious materials are suggested to improve long-term durability.